Exploring EFL Students’ Success Attributions in an Online Academic Listening Class - Suwandi, Ruth Cinthya (Journal of English and Education (JEE), 2023)
Listening is one of the important skills in English as a Foreign Language (EFL) learning and also plays an essential part in the learning process. Even though listening is vital, many EFL students feel that listening is one of the most challenging skills to learn, specifically when dealing with academic listening. This study explores attributions that help students succeed in their academic listening class that was conducted in an online learning environment. The researcher conducted a semi-structured interview with five university students at a private university in Central Java, Indonesia. The findings found out that teacher’s roles, self-efficacy and motivation and the use of technology in online learning help students to pass and gain good grades in an online Academic Listening class. The results are expected to benefit EFL teachers in finding practical ideas to enhance their students’ motivation in the academic listening class and EFL students in finding ways to be successful in their academic listening class. Practical recommendations for EFL teachers and students as well as directions for future research are presented.